Probiotic properties and antimicrobial evaluation of silymarin-enriched Lactobacillus bacteria isolated from traditional curd - Babak Haghshenas; Amir Kiani; Saeideh Mansoori; Ehsan Mohammadi-noori; Yousef Nami (Scientific Reports, 2023)
Abstract Nowadays, the increasing use of medicinal plants in the treatment and prevention of diseases has attracted the attention of researchers. The aim of this work was to investigate the probiotic properties and antibacterial and antifungal activity of silymarin-enriched Lactobacillus bacteria against several important pathogenic bacteria and also Aspergillus flavus as one of the harmful molds in the food and health industries. For this purpose, 52 g-positive and catalase-negative bacteria were isolated from 60 traditional curd samples from Ilam province. Five of the 52 bacterial strains had more than 90% viability in high bile salt and acidic conditions and were selected for further investigation. The five strains with positive results showed good hydrophobicity (≥ 50.30%), auto-aggregation (≥ 53.70%), coaggregation (≥ 28.20%), and high cholesterol removal ability (from 09.20 to 67.20%) and therefore can be considered potential probiotics. The tested strains displayed acceptable antibacterial and antifungal activity against all 12 pathogenic bacteria and A. flavus. Also, the results of the simultaneous antifungal activity of probiotic strains and silymarin showed that the combination of silymarin and probiotics has a significantly better (P < 0.05) antifungal effect than the control group or the probiotic groups alone. Interestingly, in addition to the Limosilactobacillus fermentum C3 strain, the Limosilactobacillus fermentum C18 and Lactiplantibacillus pentosus C20 strains also had significant inhibitory effects against A. flavus when used with silymarin extract in methanol. Meanwhile, silymarin extract in DMSO and PEG increased the antagonistic activity of all five potential probiotic strains.